2019
DOI: 10.5194/acp-19-13535-2019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and quantification of ENSO-linked changes in the tropical Atlantic cloud vertical distribution using 14 years of MODIS observations

Abstract: Abstract. A total of 14 years (September 2002 to September 2016) of Aqua Moderate Resolution Imaging Spectroradiometer (MODIS) monthly mean cloud data are used to quantify possible changes in the cloud vertical distribution over the tropical Atlantic. For the analysis multiple linear regression techniques are used. For the investigated time period significant linear changes were found in the domain-averaged cloud-top height (CTH) (−178 m per decade), the high-cloud fraction (HCF) (−0.0006 per decade), and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…3 h). Clear positive (negative) spikes can also be observed in the Atlantic Ocean time series during extreme El Niño (La Niña) events, which is consistent with previous findings 45 .…”
Section: Resultssupporting
confidence: 92%
“…3 h). Clear positive (negative) spikes can also be observed in the Atlantic Ocean time series during extreme El Niño (La Niña) events, which is consistent with previous findings 45 .…”
Section: Resultssupporting
confidence: 92%
“…However, the effect of ENSO on temperature and clouds extends throughout the globe [9 -11]. It affects the dynamic and thermodynamic conditions [12], thereby modulating the formation, development, and properties of clouds and CRE (e.g., [13][14][15][16]). Satellite observations and reanalysis data have shown that ENSO is a primary driver governing the variability in CF over the last several decades [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…ENSO has an effect on seasonal rainfall in East Asian by inducing a weaker and later onset of the Indian monsoon circulation (Dai and Wigley, 2000;Zhao et al, 2010;Yan et al, 2018). Vertical cloud anomalies in the tropical Atlantic from Aqua Moderate Resolution Imaging Spectroradiometer are linked to ENSO-induced shift and weakening of the Walker circulation and Hadley cell near the equator (Madenach et al, 2019). The strong 1997/98 El Niño resulted in cloud structure anomalies and their radiative property changes over the tropical Pacific (Sun et al, 2012), and increased upper tropospheric cirrus over the mid-Pacific but decreased cirrus over Indonesia (Massie et al, 2000).…”
Section: Introductionmentioning
confidence: 99%